Pemanfaatan Ulat Jerman (Zophobas Morio) dalam Mengurangi Berat Sampah Plastik - Muhammad Farrel Alfirdaus; Muchsin Riviwanto; Lindawati Lindawati; Mahaza Mahaza (Jurnal Kesehatan Lingkungan Mandiri, 2025)
Global plastic production, which reached 413.8 million tons in 2023, has led to an increase in inorganic waste that is difficult to decompose. This issue calls for environmentally friendly and low-cost alternative solutions. This study aims to determine the ability of Superworms (Zophobas morio) to reduce the weight of plastic waste through the biodegradation process. The research used a quasi-experimental design with treatments on three types of plastic waste, namely High-Density Polyethylene (HDPE), Low-Density Polyethylene (LDPE), and Expanded Polystyrene (EPS), utilizing 200 Superworm larvae over a 30-day period. Observations were conducted every five days to measure changes in waste weight. The results showed that Superworms were able to reduce HDPE by 10.2%, LDPE by 11.8%, and EPS by 66.6%. These findings indicate that Superworms have strong potential as an effective natural biodegradation agent in reducing plastic waste, particularly styrofoam, making them an innovative solution for sustainable waste management. **Conclusion: The use of Superworms has proven effective in reducing plastic waste weight, especially styrofoam. It is recommended to optimize environmental conditions such as temperature and humidity, reduce larval mortality, and study the safety and potential use of Superworms that have consumed plastic to ensure broader and ecologically safe application.